Qualitative methods for health research - Green, Judith 1961-; Thorogood, Nicki 1964- (Los Angeles SAGE, 2018)
This is a practical introduction to designing, conducting and appraising qualitative research in areas such as public health, health services research, nursing and health promotion.--
revious edition: 2014.
Includes bibliographical references (pages 389-409) and index.
Keywords: Medical care -- Research; Qualitative research -- Case studies; Qualitative research -- Methodology; Medical care -- Research -- Case studies; Medical care -- Research -- Evaluation; Qualitative Research; Research Design; Data Collection -- methods